Weight and Lenght of Digestive Organs of Super Native Chickens Fed of Amorphophallus companulatus Tuber Flour - D. T. Tabun; T. N. I. Koni; T. A. Y. Foenay; M. D. S. Randu (Jurnal Sain Peternakan Indonesia, 2021)
The purpose of this study was to examine the use of Amorphophallus companulatus (AC) tuber flour in feed on the weight and length of the digestive organs of super-native chickens. This research was conducted for 8 weeks. The experimental design used was a completely randomized design (CRD) with 4 treatments and 5 replications (P0 = feed without AC tuber flour, P1 = feed containing 5% AC tuber flour, P2 = feed containing AC tuber flour 7.5%, and P3 = feed containing 10% AC tuber flour). The results showed that the use of AC tuber flour in the super free-range chicken feed had a very significant effect (P<0.01) on the weight and length of the small intestine and significantly (P<0.05) on pancreatic weight, but had no effect (P>0 .05) against gizzard. It was concluded that AC bulbs could be used up to 10% in super-free-range chicken feed. the use of AC tuber flour as much as 7.5% in super free-range chicken feed resulted in the highest intestinal weight, intestinal length, and pancreas weight.